Dataset associated with "Role modeling is a viable retention strategy for undergraduate women in the geosciences" - Hernandez, Paul; Bloodhart, Brittany; Adams, Amanda S.; Barnes, Rebecca T.; Burt, Melissa; Clinton, Sandra M.; Du, Wenyi; Godfrey, Elaine; Henderson, Heather; Pollack, Ilana B.; Fischer, Emily V. (Colorado State University. Libraries, 2018)
Gender diversity leads to better science; however, a number of STEM disciplines, including many geoscience sub-disciplines show a persistent gender gap. PROmoting Geoscience Research, Education, and SuccesS (PROGRESS) is a theory-driven role modeling and mentoring program aimed at supporting undergraduate women interested in geoscience-related degree and career pathways. This study is unique because it is being conducted in a long-term applied setting, rather than as a laboratory exercise. We compare female STEM majors in PROGRESS to a matched control group (N = 380) using a longitudinal prospective multi-site quasi-experimental design. College women in PROGRESS participated in a mentoring and role modeling weekend workshop with follow-up support, while women in the control group participated in neither the workshop nor the follow-up support. PROGRESS members identified more female STEM career role models than controls (60% vs. 42%, respectively), suggesting that deliberate interventions can develop the networks of undergraduate women. Undergraduate women that participate in PROGRESS have higher rates of persistence in geoscience-related majors (95% vs. 73%), although the rates of switching into a geoscience-related major did not differ across groups. More strikingly, we also find that the persistence of undergraduate women in geoscience-related majors is related to the number of female STEM career role models they identify, as their odds of persisting approximately doubles for each role model they identify. We conclude that our ability to retain undergraduate women in the geosciences will depend, in part, on helping them to identify same-gender career role models. Further, the success of PROGRESS points to steps universities and departments can take to sustain their students' interest and persistence, such as hosting interactive panels with diverse female scientists to promote the attainability and social relevance of geoscience careers.
Comma separated values data file contains survey data on the demographic characteristics, measures of group assignment (PROGRESS or control), role models, and measures of holding a geoscience-related major for study participants (n=380). These data were collected between 2015 / 2016 (time at which participants were recruited into the study) and 2017 (date of follow-up survey). Data are provided here for the purpose of making data reported in the journal article "Role Modeling is a Viable Retention Strategy for Undergraduate Women in the Geosciences," open and publicly accessible for posterity and potential use in future scientific study – such as meta-analysis.
Department of Atmospheric Science
Walter Scott, Jr. College of Engineering
Keywords: female; gender; STEM; geoscience; role model; persistence